Feasibility and outcome of genomics-guided treatment selection in advanced cancer – the MEGALiT explorative clinical trial - Lars Ny; Henrik Fagman; Johan Botling; Loviisa Mantovaara; Peter Asplund; Hannah Karlsson; Jennie Aust; Edvard Abel; Mats Hellström; Joakim Crona; Peter Nygren (Acta Oncologica)
Background: Precision cancer medicine (PCM) is key to advancing cancer treatment beyond the standard of care. We performed an explorative clinical trial, MEGALiT, to investigate the feasibility, safety, and clinical benefit of genomics-based PCM in advanced cancer.